The Homologies of Spontaneous and Induced Temperature-sensitive Mutants of Vesicular Stomatitis Virus Isolated in Chick Embryo and BHK 21 Cells - Flamand, Anne; Pringle, C. R. (Journal of General Virology, 1971)
Summary A series of 71 spontaneous temperature-sensitive mutants of vesicular stomatitis virus (type indiana) have been isolated in chick embryo cells (Flamand, 1970). In addition, 175 induced mutants have been isolated from a different wild-type strain propagated in BHK 21 cells (Pringle 1970b). These mutants have been classified into complementation groups independently. Reciprocal complementation experiments are now described which establish the genetic homologies of these mutants. The results obtained in the two systems are in good agreement, despite differences in experimental procedure, restrictive temperature, wild-type strain and host cell. It can be concluded that complementation groups I–IV in the Glasgow classification correspond to the groups represented by ts 4, ts 52, ts 23 and ts 100 in the Orsay system. Mutant ts 45 (Orsay) belongs to a fifth group not represented among the Glasgow mutants.